The relationship between anxiety and emotional distress in nicotine addiction - Angelescu, Andreea Elena; Sandu, Mihaela Luminița (Eximia, 2023)
This study investigates the interrelationship between anxiety and emotional distress in the context of nicotine addiction. Multivariate statistical analysis was applied to determine whether anticipatory anxiety is associated with increased levels of emotional distress, and whether this association is mediated by severity of nicotine dependence. Results indicate a significant correlation between anxiety and emotional distress, with nicotine dependence serving as a partial mediator. These findings suggest that clinical interventions designed to reduce anxiety may play a key role in reducing emotional distress and potentially facilitating smoking cessation. The study contributes to the existing literature by emphasizing the importance of addressing psychological comorbidity in the treatment of nicotine addiction and provides insight for the development of more effective therapeutic strategies.